Improved accuracy and precision with three‐parameter simultaneous myocardial T1 and T2 mapping using multiparametric SASHA. Issue 6 (8th February 2022) - Chow, Kelvin; Hayes, Genevieve; Flewitt, Jacqueline A.; Feuchter, Patricia; Lydell, Carmen; Howarth, Andrew; Pagano, Joseph J.; Thompson, Richard B.; Kellman, Peter; White, James A.
Abstract : Purpose: To develop and validate a three‐parameter model for improved precision multiparametric SAturation‐recovery single‐SHot Acquisition (mSASHA) cardiac T1 and T2 mapping with high accuracy in a single breath‐hold. Methods: The mSASHA acquisition consists of nine images of variable saturation recovery and T2 preparation in 11 heartbeats with T1 and T2 values calculated using a three‐parameter model. It was validated in simulations and phantoms at 3 T with comparison to a four‐parameter joint T1 ‐T2 technique. The mSASHA acquisition was compared with MOLLI, SASHA, and T2 ‐prepared balanced SSFP in 10 volunteers. Results: The mSASHA technique had high accuracy in phantoms compared to spin echo, with −0.2 ± 0.3% T1 error and −2.4 ± 1.3% T2 error. The mSASHA coefficient of variation in phantoms for T1 was similar to MOLLI (0.7 ± 0.2% for both) and T2 ‐prepared balanced SSFP for T2 (1.3 ± 0.7% vs 1.4 ± 0.3%, adjusted p > .05 for both). In simulations, three‐parameter mSASHA had higher precision than four‐parameter joint T1 ‐T2 for both T1 and T2 (46% and 11% reductions in T1 and T2 interquartile range for native myocardium). In vivo myocardial mSASHA T1 was similar to SASHA (1523 ± 18 ms vs 1520 ± 18 ms) with similar coefficient of variation to both MOLLI and SASHA (3.3 ± 0.6% vs 3.1 ± 0.6% and 3.3 ± 0.5% respectively, adjusted p > .05 for all). Myocardial mSASHA T2 was 37.1 ± 1.1 ms with similar precision to T2 ‐prepared balanced SSFP (6.7 ± 1.7% vs 6.0 ± 1.6%, adjusted p > .05). Conclusion: Three‐parameter mSASHA provides high‐accuracy cardiac T1 and T2 quantification in a single breath‐hold with similar precision to MOLLI and T2 ‐prepared balanced SSFP. Further study is required to both establish normative values and demonstrate clinical utility in patient populations.